Effect of Chitosan-Beeswax Edible Coating on Microbiological Profile of Chicken Thigh Meat at Freezer Storage - Salwa Haneefah Fauzia; Dedi Fardiaz; Laprianika Retha Hapita Sari; Dewi Masyithoh (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
This research examined the effect of chitosan and beeswax edible coating with different percentages on the microbiological value (aerobic bacteria, Staphylococcus aureus, Coliform, and Escherichia coli) of chicken thigh meat in two days of storage at freezer temperature (-18oC to -20oC). The study used Completely Randomized Design with 4 treatments and 5 replications. Treatments included were A0 (control), A1 (chitosan 2%), A2 (chitosan 2% + beeswax 1%), and A3 (chitosan 2% + beeswax 2%). Variables observed were the number of aerobic bacteria, S. aureus, Coliform, and E. coli using 3MTM PetrifilmTM Plates. Results showed significant differences (p<0.05) in the number of aerobic bacteria colonies with the least colony on treatment A1. S. aureus and Coliform colonies showed significant differences (p<0.05) with the least colony on treatment A2 and A3, sequentially. There was no significant difference (p>0.05) in E. coli count due to no colonies detected on all treated samples. However, compared to controlled samples, it was found to decrease. The decrease in colony numbers shows that edible coating treatments can be used to help preserve or extend the shelf life of chicken thigh meat.